Analysis of Employee Placement and Its Effect on Employee Performance at the Personnel and Human Resource Development Agency of Simalungun Regency in 2025 - Adrian K Tarigan; Yeni Trisna Purba; Diana Florenta Butar-butar (Economic: Journal Economic and Business, 2025)
This study aims to analyze the relationship between employee placement and employee performance at the Pematangsiantar City Regional Secretariat. This study uses a qualitative descriptive approach, with data collection conducted through documents and questionnaires distributed to employees. The results of the study indicate that employee placement has a significant relationship with their performance. Factors such as education level, knowledge, skills, and work experience play an important role in improving the quality of work, work quantity, and timeliness of employees in completing their tasks and responsibilities. However, employee placement at the Pematangsiantar City Regional Secretariat is not yet fully optimal because there are still employees who are placed in an inappropriate educational background or age that does not support the position. This study provides recommendations for the employee placement process to pay more attention to appropriate qualifications to improve the effectiveness of organizational performance.